Antimicrobial Peptide from the Wild Bee Hylaeus signatus Venom and Its Analogues: Structure-Activity Study and Synergistic Effect with Antibiotics - Nešuta, Ondřej; Hexnerová, Rozálie; Buděšínský, Miloš; Slaninová, Jiřina; Bednárová, Lucie; Hadravová, Romana; Straka, Jakub; Veverka, Václav; Čeřovský, Václav (Journal of natural products, 2016)
Venoms of hymenopteran insects have attracted considerable interest as a source of cationic antimicrobial peptides (AMPs). In the venom of the solitary bee Hylaeus signatus (Hymenoptera: Colletidae), we identified a new hexadecapeptide of sequence Gly-Ile-Met-Ser-Ser-Leu-Met-Lys-Lys-Leu-Ala-Ala-His-Ile-Ala-Lys-NH2. Named HYL, it belongs to the category of α-helical amphipathic AMPs. HYL exhibited weak antimicrobial activity against several strains of pathogenic bacteria and moderate activity against Candida albicans, but its hemolytic activity against human red blood cells was low. We prepared a set of HYL analogues to evaluate the effects of structural modifications on its biological activity and to increase its potency against pathogenic bacteria. This produced several analogues exhibiting significantly greater activity compared to HYL against strains of both Staphylococcus aureus and Pseudomonas aeruginosa even as their hemolytic activity remained low. Studying synergism of HYL peptides and conventional antibiotics showed the peptides act synergistically and preferentially in combination with rifampicin. Fluorescent dye propidium iodide uptake showed the tested peptides were able to facilitate entrance of antibiotics into the cytoplasm by permeabilization of the outer and inner bacterial cell membrane of P. aeruginosa. Transmission electron microscopy revealed that treatment of P. aeruginosa with one of the HYL analogues caused total disintegration of bacterial cells. NMR spectroscopy was used to elucidate the structure-activity relationship for the effect of amino acid residue substitution in HYL.
Keywords: kationické antimikrobiální peptidy; Microbial Sensitivity Tests; Staphylococcus aureus; Humans; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; Nuclear Magnetic Resonance, Biomolecular; nukleární magnetická rezonance biomolekulární; Bee Venoms; mikrobiální testy citlivosti; lidé; antibakteriální látky; zvířata; včely; molekulární struktura; Pseudomonas aeruginosa; Antimicrobial Cationic Peptides; Molecular Structure; Anti-Bacterial Agents; Bees; Animals; včelí jedy